2019
DOI: 10.1080/13803395.2019.1611742
|View full text |Cite
|
Sign up to set email alerts
|

Priming older adults and people with Alzheimer’s disease analogical problem-solving with true and false memories

Abstract: We investigated the extent to which activation of specific information in associative networks during a memory task could facilitate subsequent analogical problem solving in healthy older adults as well as those with early onset Alzheimer's disease. We also examined whether these priming effects were stronger when the activation of the critical solution term during the memory task occurred when the item was actually presented (true memories) or when this item arose due to spreading activation to a related but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Here, participants are shown degraded representations of pictures of objects or words and tried to identify them as quickly as possible. In other problem-solving tasks (i.e., CRATs and analogies), both older adults and people with Alzheimer’s disease benefit from having formed a false memory in a prior list-learning task when the false memory is also the solution to the problem (Akhtar et al, 2018; Akhtar & Howe, 2019; Howe & Akhtar, 2020). In fact, false memories tend to serve as better primes than true memories in these tasks (e.g., see Howe et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Here, participants are shown degraded representations of pictures of objects or words and tried to identify them as quickly as possible. In other problem-solving tasks (i.e., CRATs and analogies), both older adults and people with Alzheimer’s disease benefit from having formed a false memory in a prior list-learning task when the false memory is also the solution to the problem (Akhtar et al, 2018; Akhtar & Howe, 2019; Howe & Akhtar, 2020). In fact, false memories tend to serve as better primes than true memories in these tasks (e.g., see Howe et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that people with early onset AD exhibit the same rate of false memories as older adult controls (OACs) for verbal stimuli (Akhtar et al, 2018; Akhtar & Howe, 2019; Howe & Akhtar, 2020). However, other studies have shown the reverse effect, particularly with mild AD patients (e.g., Balota et al, 1999).…”
Section: The Present Studymentioning
confidence: 99%
See 3 more Smart Citations